1989
DOI: 10.1099/00222615-29-3-171
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of the Bacteroides fragilis group in the colonic flora in 10 patients with colonic cancer

Abstract: Summary. We report the relative frequencies of members of the Bacteroides fragilis group in the faeces, in colon lavage fluid obtained pre-operatively, and in colonic tissue specimens obtained at operation from 10 patients with colonic cancer. B. vulgatus was the most and B. fragilis and B. ovatus were the least frequently isolated Bacteroides spp. in the faeces of the 10 subjects. B. uniformis and B. thetaiotaomicron ranked second and third in the faeces. The relative frequencies of all species except B. frag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 12 publications
(3 reference statements)
1
22
0
Order By: Relevance
“…The Don system must have evolved to assist in the establishment of a specific niche in the gut or to help the organism maintain its competitive position. Several studies have indicated that B. fragilis are closely associated with the mucosa, and that they penetrate the mucus layer to bind receptors deep in the crypts (23,24). The don genes are significantly induced by a crude mixture of gastric mucin glycans and in fact, they were the most highly induced of all genes in mucin glycan medium (SI Appendix, Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…The Don system must have evolved to assist in the establishment of a specific niche in the gut or to help the organism maintain its competitive position. Several studies have indicated that B. fragilis are closely associated with the mucosa, and that they penetrate the mucus layer to bind receptors deep in the crypts (23,24). The don genes are significantly induced by a crude mixture of gastric mucin glycans and in fact, they were the most highly induced of all genes in mucin glycan medium (SI Appendix, Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…Bacteroides fragilis are commensals colonizing the majority of humans and are the most frequent Bacteroides species identified at the mucosal surface of the colon where they probably contribute to intestinal homeostasis (Moore and Holdeman, 1974;Namavar et al, 1989;Hooper and Gordon, 2001;Coyne et al, 2005). Virulence of B. fragilis is ascribed, in part, to the unparalleled diversity of the polysaccharide capsule (Krinos et al, 2001) and, for ETBF strains, to the production of a zinc-dependent metalloprotease toxin termed BFT (Sears, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation of the intestinal tract caused by Campylobacter jejuni, Helicobacter pylori, and many other pathogens results in increased levels of oxidative stress within the epithelial layer and the intestinal tract (46)(47)(48)(49). B. fragilis is closely associated with the intestinal epithelium, which has been shown to incur significant DNA damage from reactive oxygen species from the host immune response (47,50,51). Additionally, it has been shown that an oxygen concentration gradient exists extending out from the epithelial surface, so that B. fragilis may be exposed to an environment with as much as 8% oxygen, depending on the precise site of colonization (51,52).…”
Section: Discussionmentioning
confidence: 99%